Climate Change, Urbanization, and the Future of Rural Health: Addressing Challenges and Opportunities - Sankha Randenikumara; Ejaz Ahmad Khan; Anshu; Mandisa Ndlovu-Tenego; Oleksii Korzh; Nisanth Menon Nedungalaparambil; Smruti Haval; Dewanto Andoko; M. I. Mohamed Shuja; Joseph Scott-Jones; Waseem N. Ahmed; Ozden Gokdemir; et al. (Journal of Surgical Specialties and Rural Practice)
Rural communities in low- and middle-income countries (LMICs) are particularly vulnerable to escalating health challenges driven by climate change and rapid urbanization. Limited healthcare infrastructure, economic instability, and inadequate access to climate information exacerbate health disparities. Climate change intensifies rural vulnerabilities by increasing extreme weather events, food and water insecurity, and the spread of diseases. Simultaneously, urbanization drives overcrowded informal settlements, strains health systems, and widens the urban–rural health gap. The migration of healthcare professionals to cities further weakens rural health care. This paper explores interdisciplinary solutions to strengthen rural healthcare systems, promote sustainable urban planning, and implement policies to mitigate health inequities. Key strategies include investing in climate-resilient health infrastructure, expanding telemedicine and mobile health technologies, and fostering community-based healthcare models. Climate-adaptive agricultural practices and equitable policy interventions are essential to ensuring long-term sustainability. Addressing these challenges requires coordinated efforts from governments, international organizations, and researchers to develop data-driven, context-specific solutions. Integrating climate adaptation into health planning can help LMICs build resilient, inclusive healthcare systems that protect vulnerable populations from climate and urbanization-related risks. Family doctors working within primary healthcare teams have a unique opportunity to work with individuals to enhance their knowledge of the impact climate change has upon their health, within teams to reduce carbon emissions, with communities to mitigate and adapt to climate challenges, and with society to advocate for the multimodal policy and practice changes that are required in the face of the climate crisis.